Reinventing government and reformulating public administration - Gargan, John J. (1997)
The National Performance Review is the most recent of a succession of major public sector reform initiatives. The conceptual base of the Review draws from Osborne and Gaebler and competitive market models of administration. This article discusses the relevance of the base and models, given the current responsibilities of the national government. An alternative concept, governing capacity, is proposed as the appropriate theoretical focus for the study of public administration. - Reproduced
Keywords: Public administration